Influence of air flow rate on emission of DEHP from vinyl flooring in the emission cell FLEC: Measurements and CFD simulation - Clausen, Per Axel; Liu, Zhe; Xu, Ying; Kofoed-Sørensen, Vivi; Little, John C. (Atmospheric environment (1994), 2010)
The emission of di-(2-ethylhexyl)phthalate (DEHP) from one type of vinyl flooring with ∼15% (w/w) DEHP as plasticizer was measured at 22 °C in five FLECs + one blank FLEC (Field and Laboratory Emission Cell). Initially, the flow through all FLECs was 450 ml min −1. After 689 days the flows were changed to 1000 ml min −1, 1600 ml min −1, 2300 ml min −1, and 3000 ml min −1, respectively, in four FLECs, and kept at 450 ml min −1 in one FLEC. Air samples were collected from the effluent air at regular intervals. After 1190 days the experiments were terminated and the interior surfaces of all six FLECs were rinsed with methanol to estimate the internal surface concentrations of DEHP. The DEHP air concentration and specific emission rate (SER) at steady state was estimated for the five different flow rates. The steady-state concentrations decreased slightly with increasing air flow with only the two highest flow rates resulting in significantly lower concentrations. In contrast, the SERs increased significantly. Despite large variation, the internal surface concentrations appeared to decrease slightly with increasing FLEC flow. Computational fluid dynamic (CFD) simulations suggest that the interior gas and surface concentrations were roughly uniform for the low flow case (450 ml min −1), under which, the partitioning between the FLEC internal surface and chamber air was examined. Although paired t-tests showed no difference between CFD and experimental results for DEHP air concentrations and SERs at steady-state conditions, CFD indicated that the experimental DEHP surface concentrations in the FLECs were underestimated. In conclusion, the experiments showed that the emission of DEHP from vinyl flooring is subject to “external” control and that the SER is strongly and positively dependent on the air exchange rate. However, the increased SER almost compensates for the decrease in gas-phase concentration caused by the increased air exchange.